TANGGUH BENCANA MELALUI RENCANA KONTINGENSI DAN BANTUAN SOSIAL PADA KELOMPOK RENTAN DENGAN SERVICE EXELLENT DI WILAYAH KERJA PUSKESMAS KAMPUNG BARU KOTA MEDAN TAHUN 2024 - Lasria Simamora; Rosmani Sinaga; Sonia Novita Sari; Erin Padilah; Nurmalina Hutahaean; Ika Damayanti Sipayung; Damayanty S; Jusnita; Khairani Munthe; Endang Panjaitan (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
Disaster contingency plans and social assistance are plans that contain efforts to deal with the threat of disaster. This plan is part of the Disaster Emergency Management Plan (RPKB) and can be turned into a Disaster Emergency Operation Plan (RODB) when a disaster emergency occurs. Recurrent flooding incidents in the working area of ​​the Kampung Baru Community Health Center are of particular concern. This requires the community to have adequate disaster management skills, especially vulnerable groups. Therefore, Community Service for Disaster Resilience through contingency plans for vulnerable groups in the Working Area of ​​the Kampung Baru Community Health Center, Medan City, North Sumatra Province needs to be carried out. This service is carried out through preparation, implementation and evaluation methods. Participants consisted of 40 people from vulnerable groups. This activity was held on campus Jl. Brigadier General Katamso Gg. Lamp I Below Ward XVI Medan City. The results of the service showed that at the pretest, all participants did not know about disaster response, and at the posttest, 15 participants (46.9%) experienced an increase in their knowledge to be good and sufficient..